If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -7x = 36 + -14x Solving 13 + -7x = 36 + -14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14x' to each side of the equation. 13 + -7x + 14x = 36 + -14x + 14x Combine like terms: -7x + 14x = 7x 13 + 7x = 36 + -14x + 14x Combine like terms: -14x + 14x = 0 13 + 7x = 36 + 0 13 + 7x = 36 Add '-13' to each side of the equation. 13 + -13 + 7x = 36 + -13 Combine like terms: 13 + -13 = 0 0 + 7x = 36 + -13 7x = 36 + -13 Combine like terms: 36 + -13 = 23 7x = 23 Divide each side by '7'. x = 3.285714286 Simplifying x = 3.285714286
| -4(3b+3)+(13b-7)=0 | | 3x-8=4x-5 | | (3x^2+14x+24)=0 | | 4+5t-3=9t+3-2t | | 6x+13=-92-9 | | 93-6x=12x+15 | | x-1,833=-2 | | 2*(6-2)^2-(7*2+1)/3 | | 2x+14=-36-10x | | 4(3x^2+14x+24)=0 | | 3(2x-4)+8x=4(3x-4)+5x+1 | | 12x+8=280 | | 15*35= | | y+2/5=7/10 | | 15(35)= | | 4b-1/7=5/7 | | 3X+1Y=90 | | 7+4x-10x+15= | | 3/5c=1/4(2-3c) | | 12n+60=1440 | | 9x=169 | | 2+8x=86+11 | | 9x=1691 | | x+13=-71-10x | | 3500/15 | | 1/4x+7+17 | | 17.895*0.4= | | 7(t-2)+5t=4(3t+4)-11 | | 45y^2-20x^2=0 | | 84-2x+5x=7 | | 4c*2e= | | Cx+Fx=L |